Pembelajaran Think Pair Share (TPS) sebagai Upaya Meningkatkan Berpikir Kritis dan Motivasi Belajar - Ninik Tri Kusumadewi; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2022)
Motivation is an encouragement or strength that can lead to a positive level of willingness for a person or study group and make a person study learn harder, more persistently and actively in the learning process. However, several surveys state that the motivation of students in learning is still low, therefore there is a need for a change that makes learning more interesting and increases the motivation and critical thinking of students. Innovation in the field of education continues to be carried out by the government to support the times. Many things can be developed in the learning innovation process, including from the aspect of educators, students, learning resources, and educational units. One of them is a cooperative learning model that can be developed in the Think Pair Share (TPS) type of learning process. The learning model is an effective way to create variations in the atmosphere of class discussion patterns. Think Pair Share (TPS) of exchange ideas with a partner is a type of cooperative learning designed to influence student interaction pattern. With the Think Pair Share model, especially in social studies lessons, students will be able to develop critical thinking skills and answer in communication with one another, as well as work to help each other in small groups. The method used in this study is a qualitative, descriptive research method with a library approach, namely by browsing the literature relevant to the topic of discussion. The results of this study indicate that the influence of the TPS learning model on student’s critical thinking.